Sales management, education, and scholarship across cultures: early findings from a global study and an agenda for future research. Issue 3 (2nd July 2020) - Dugan, Riley; Rangarajan, Deva; Davis, Lenita; Bolander, Willy; Pullins, Ellen Bolman; Deeter-Schmelz, Dawn; LeBon, Joel; Agnihotri, Raj
Abstract: While interest from the practitioner community in topics pertaining to global sales forces continues to accelerate, academic sales research that examines the challenges faced by these salespeople and their firms continues to lag behind. In response, the American Marketing Association (AMA) Sales Special Interest Group (Sales SIG) has recently developed an initiative designed to increase access to global sales force data. The initiative provides periodic, "snapshots" of the profession, via survey data, that can be used to guide sales scholars' research agendas and provide critical insight into challenges facing salespeople across the globe. Recently, a group of sales scholars gathered to discuss the initial survey results from B2B salespeople in the United Kingdom, the Netherlands, Australia, and India. This manuscript reveals the interesting commonalities—and distinctions—between salespeople in those various countries on issues related to turnover, education and training, compensation, bureaucracy, technology usage, ethics, and macro-level challenges. Additionally, a subsequent discussion of the results, which we detail in this manuscript, reveals fruitful and important future research opportunities for sales scholars interested in global sales research.